Digital image analysis of immunohistochemistry KI-67 using QuPath software in breast cancer - Hermin Aminah Usman; Fauzan Ali Zainal Abidin (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: Today, pathology services are more developed for quantitative diagnostic evaluation. The quantitative diagnostic evaluation requires detailed accuracy and can be done using digital image analysis (DIA). Assessment of the Ki67 labelling index (LI) in breast carcinoma needs to be done quantitatively. A visual evaluation of Ki67 LI using light microscopy has high inter-observer variability. The evaluation of Ki67 LI could be done digitally with the DIA technique to overcome the inter-observer variability. The DIA technique is carried out by counting the Ki67 LI manually or automatically with bioimage analysis software. QuPath is one of the bioimage analysis software, has characteristics of cross-platform, intended for bioimage analysis and digital pathology.Objective: This study aims to compare the manual and automatic calculation of Ki67 LI digitally. Methods: This study was a cross-sectional study; a total of 240 digital Ki67 images from 30 slides were analyzed by counting manually and automatically using QuPath. Results: Statistical analysis using the T-test showed no significant difference between the manual and automatic counting of Ki67 LI (p = 0,801, a = 0,05). Conclusion: Digital image analysis using QuPath can be used to calculate the Ki67 LI automatically.